Diachronic Construction Grammar - Barðdal, Jóhanna; Smirnova, Elena; Sommerer, Lotte; Gildea, Spike (John Benjamins, 2015)
Construction Grammar as a framework offers a new perspective on traditional historical questions in diachronic linguistics and language change: how do new constructions arise, how should competition in diachronic variation be accounted for, how do constructions fall into disuse, and how do constructions change in general, formally and/or semantically, and with what implications for the language system as a whole? This volume offers a broad introduction to the confluence of Construction Grammar and historical syntax, and also detailed case studies of various instances of syntactic change modeled within Construction Grammar. The volume demonstrates that Construction Grammar as a theory is particularly well suited for modeling historical changes in morphosyntax, and it also documents challenging new phenomena that require a theoretical account within any competing framework of syntactic chang
Keywords: Cognition and language; Historical linguistics; Syntax; Theoretical linguistics